Becoming Overweight without Gaining a Pound: Weight Evaluations and the Social Integration of Mexicans in the United States1. Issue 1 (8th December 2015) - Altman, Claire E.; Van Hook, Jennifer; Gonzalez, Jonathan
Abstract : Mexican women gain weight with increasing duration in the United States. In the United States, body dissatisfaction tends to be associated with depression, disordered eating, and incongruent weight evaluations, particularly among white women and women of higher socioeconomic status. However, it remains unclear how being overweight and obesity are interpreted by Mexican women. Using comparable data of women aged 20–64 from both Mexico (the 2006 Encuesta Nacional de Salud y Nutricion; N = 17, 012) and the United States (the 1999–2009 National Health and Nutrition Examination Surveys; N = 8, 487), we compare weight status evaluations among Mexican nationals, Mexican immigrants, US‐born Mexicans, US‐born non‐Hispanic whites, and US‐born non‐Hispanic blacks. Logistic regression analyses, which control for demographic and socioeconomic variables and measured body mass index and adjust for the likelihood of migration for Mexican nationals, indicate that the tendency to self‐evaluate as overweight among Mexicans converges with levels among non‐Hispanic whites and diverges from blacks over time in the United States. Overall, the results suggest a US integration process in which Mexican‐American women's less critical self‐evaluations originate in Mexico but fade with time in the United States as they gradually adopt US white norms for thinner body sizes. These results are discussed in light of prior research about social comparison and negative health assimilation.